Association of exposure to multiple volatile organic compounds with ultrasound-defined hepatic steatosis and fibrosis in the adult US population: NHANES 2017–2020 - Wentao Shao; Wentao Shao; Pan Gong; Qihan Wang; Fan Ding; Weiyi Shen; Hongchao Zhang; Anhua Huang; Chengyu Liu (Frontiers in Public Health)
ObjectiveVolatile organic compounds (VOCs) are pervasive environmental pollutants known to impact human health, but their role in liver steatosis or fibrosis is not fully understood. This study investigates the association of urinary VOC mixtures with the risk of liver steatosis and fibrosis in U.S. adult population.MethodsData of 1854 adults from the National Health and Nutrition Examination Survey (NHANES) from 2017.01 to 2020.03 were collected. Vibration Controlled Transient Elastography (VCTE) assessed hepatic steatosis and liver fibrosis via the controlled attenuation parameter (CAP) and liver stiffness measurement (LSM), respectively. The study examined the relationship between urinary exposure biomarkers for 20 VOCs and liver health outcomes using multivariate logistic regression and Bayesian Kernel Machine Regression (BKMR) to evaluate the effects of both individual and mixed VOC exposures.ResultsMultivariate logistic regression analysis revealed that exposure biomarkers for acrolein and crotonaldehyde were positively associated with hepatic steatosis. Conversely, biomarkers for styrene, ethylbenzene, and propylene oxide were negatively associated with hepatic steatosis. Furthermore, biomarkers for 1,3-butadiene and xylene were positively associated with liver fibrosis, while ethylbenzene was negatively associated with this condition. BKMR analysis identified a significant positive joint effect of VOC biomarkers on CAP. Notably, when other VOC-EBs were held at median levels, biomarkers for acrolein and 1,3-butadiene exhibited linear correlations with Ln CAP and hepatic Ln LSM, respectively.ConclusionThe study highlights the potential hepatotoxic effects of VOC mixtures, particularly noting the roles of acrolein and 1,3-butadiene in exacerbating liver steatosis and fibrosis. These findings advocate for further research to explore the mechanistic pathways and conduct longitudinal studies to establish causality and enhance understanding of VOCs’ impact on liver health.